A Sustainable Route From Quartz to Bifunctional Material with Adsorbed Lanthanides for Enhanced Fluorescent Activation in Doxycycline Sensing - Olha Semeshko; Maksym Fizer; Valeriia Sliesarenko; Jaroslav Briancin; Oleksandr Bondarchuk; Aleksandra Lobnik; Inna Melnyk (Advanced Materials Interfaces)
Abstract A nanosized bifunctional adsorbent with diamino and phenyl groups on its surface is synthesized through the functionalization of silica derived from quartz. The composition, morphology, and particle size of the functionalized silica are characterized using various physicochemical methods. The material demonstrates high sorption properties for La(III) and Ce(III), both found in Ni‐MH batteries, as well as Eu(III). The synthesized functionalized silica, with adsorbed lanthanides, is employed for sensor‐based detection of doxycycline in aqueous solutions. After sorbing lanthanides, the bifunctional adsorbent shows a linear response to doxycycline in the concentration range of 0.005–10.0 µm, with a detection limit of 0.15 µm L−1 and a quantification limit of 0.44 µm L−1. The increase in photoluminescence signal upon the addition of doxycycline is explained using Judd–Ofelt theory. Experimental W2 and W4 parameters of the Eu‐doped nanomatrix are determined to be 1.44 × 10−20 cm2 and 8.55 × 10−20 cm2, respectively, with these values increasing to 73.40 × 10−20 cm2 and 35.58 × 10−20 cm2 upon the addition of doxycycline. A significant increase in the radiative emission rate from 196 s−1 to 1977 s−1 is observed with doxycycline addition. It is demonstrated that the system containing the three lanthanides exhibits unique sensor properties, attributed to the co‐luminescence of the Eu(III) ion.